THE INFLUENCE OF LEARNING CARD SORT STRATEGY ON HISTORY LEARNING ACHIEVEMENT OF CLASS XI STUDENTS STATE HIGH SCHOOL 1 OF LHOONG ACEH BESAR - Rika Rahmalia; T Abdullah; Nurasiah . (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2018)
The study, entitled "The Effect ofLearning Strategies Card Sort on History Learning Achievement of Class XI Students of Lhoong Aceh Besar 1 High School 1" aims to: (1) analyze the effect ofstrategies card sort on the Class XI Students' Learning Achievement in Lhoong Aceh Besar 1 High School; and (2) to explain the factors that influence student learning outcomes by using astrategy card sort towards the History Learning Achievement of Class XI Students of Lhoong Aceh Besar 1 State High School. The approach used in this study is a quantitative and qualitative approach with the type of experimental research. The population of this study were all students of class XI SMA 1 Lhoong which amounted to 85 students and consisted of 4 classes, namely 2 science classes and 2 social studies classes and the sample used was class XI science1 consisting of 20 students and XI science2 which consisted of 20 students. Data collection techniques in this study use tests, documentation, and interviews. The results obtained in this study are the Effect ofLearning Strategies Card Sort on the History Learning Achievement of Class XI Students of Lhoong Aceh Besar 1 State Senior High School. Based on the results of data processing using t-test analysis obtained the value at the level of 5% (obtained tcount = 2.34 at significant levels ( and opportunities (1-, t(0 , 95) (27) = 2.04 with dk = 28 - 1 = 27. Due to 2,34 2,04 hence, H0 is rejected and H1 accepted. And from my research there were 30% of students who did not achieve the KKM score and 70% of students who had achieved the KKM score. Factors that can influence student learning outcomes by using astrategy card sort are the direct involvement of students in the learning process. Learning by using astrategy card sort can increase student interest and motivation because students not only become passive listeners of the information conveyed by the teacher but also involve students directly in the learning process in the classroom. Keywords: Srategy Card Sort, Learning Achievement.